Comparative study of thermally integrated pumped thermal energy storage based on the organic rankine cycle with different working fluid pairs - Jiang, Xuhui; Zhang, Xi; Wang, Ruiqiong; Wang, Xurong (Frontiers in Energy Research, 2023)
Thermal integrated pumped thermal energy storage (TIPTES) systems with the features of high efficiency, flexibility, and reliability, have attracted increasing attention since they can integrate low-grade heat sources to further improve the utilization and economic viability of renewable energy. In this study, a typical TIPTES system driven by waste flue gas is established, and the heat pump and organic Rankine cycle (ORC) are chosen as the charging and discharging cycle, respectively. Four organic fluids, including R600, R245fa, R601a, and R1336mzz(Z), are selected to compose sixteen different working fluid pairs for thermodynamic analysis. The effects of key parameters, like heat pump system evaporation temperature and hot storage tank temperature, on system performance were analyzed, and the single-objective optimization was conducted. A comparative study was carried out to identify the best working fluid pair according to the optimization results. Results show that the system’s power-to-power efficiency goes up as the evaporation temperature increases while an increase in the heat storage temperature decreases the exergy efficiency of the TIPTES system. Optimization results show that the R245fa + R245fa is the best working fluid pair, and in this system, the ORC evaporator has the largest exergy destruction at about 260.84 kW, which is 20.2% of the total. On the other hand, the ORC pump has the smallest exergy destruction only about 0.5%. This study also finds that the system’s power-to-power efficiency of using different working fluids in either heat pump cycles or ORC cycles is lower than that of using the same working fluid throughout the entire system.